Determining the optimal log position during primary breakdown using internal wood scanning techniques and meta-heuristic algorithms - Van Zyl, Fritz (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Industrial Engineering))--University of Stellenbosch, 2011.